A qualitative analysis of male eating disorder symptoms. Issue 4 (8th August 2017) - Arnow, Katherine D.; Feldman, Talya; Fichtel, Elizabeth; Lin, Iris Hsiao-Jung; Egan, Amber; Lock, James; Westerman, Marcus; Darcy, Alison M.
ABSTRACT: Insights into how males experience eating disorder symptoms early in the course of illness are important to improve detection efforts and may also provide valuable information for treatment. In this qualitative study, 10 adolescent males and 10 matched female patients completed standardized questionnaires and were interviewed. Results indicated that although there were many similarities between the genders, females were more likely to describe the involvement of family systems and males were more likely to describe involvement in sports as being catalysts for their disorders. Males in this study were more positive about being in treatment.